Creative Review of Amelia Walker's Alogopoiesis - Rhodes, Kendrea (Art/Research International)

(untitled) (University of Alberta, 2024)
This review of Amelia Walker’s Alogopoiesis is an interdisciplinary response, reflecting Walker’s own creative approach of employing both form and content. Creative nonfiction, critical thinking, and a mixed media artwork response to Alogopoiesis reflect the effects that reading it has had on me as a creative, as a researcher, and as a living being. It is a happy coincidence that I chose to open the book in a café on Mount Myoko in Japan, and, as I climbed through the pages, I discovered a multitude of connections to my many worlds. I began walking beside each protagonist, nodding, feeling, staying. The word alogopoiesis, made up from alogia and poiesis, is an apt portmanteau for this body of work. Alogopoiesis renders an unsilencing. A slow-rebuild, remaking, and sensing of gaps where the unspoken reside. This book sharpened my outlook. My in-look. Replacing my rose-coloured glasses with recognition as I sank into stories of mental distress, violence, abuse, heartbreak, and prejudice.